PID controller for unmanned aerial vehicle in closed environment using fiducial marker systems - Amiri, Mohammad Soleimani; Ramli, Rizauddin; Zaidi, I. E.; Van, Mien (Penerbit UTeM, 2024)
Unmanned Aerial Vehicles (UAVs) are widely used for various purposes, including surveillance, inspection, supply delivery, and military operations. The conventional navigation technologies have deficits in accuracy and robustness in narrowed environments and do not properly support fully autonomous robotic functionalities. The aim of this paper is to develop an autonomous navigation algorithm for a UAV using a tag-based visual system. In this paper, a navigation method based on fiducial marker systems has been established. A Proportional-Integral-Derivative (PID) controller has been established to track the UAV toward the desired path. The navigation algorithm has been programmed in Python and the Robot Operating System (ROS) and implemented in a DJI Tello as an UAV application. An experimental set has been provided to validate the navigation performance. The average error of the proposed navigation system is 0.19, 0.08, and 0.83 radian in X, Y, and Z axes. The experimental results showed the efficiency and stability of the developed autonomous navigation algorithm for UAVs using the Apriltag visual system along with the PID controller. As future work, the proposed navigation system will be improved to incorporate obstacle avoidance capabilities and enhanced multi-UAV coordination in more complex environments.